2020
DOI: 10.1186/s13756-020-00860-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial prophylaxis administration after umbilical cord clamping in cesarean section and the risk of surgical site infection: a cohort study with 55,901 patients

Abstract: Background The World Health Organization (WHO) recommends administration of surgical antimicrobial prophylaxis (SAP) in cesarean section prior to incision to prevent surgical site infections (SSI). This study aimed to determine whether SAP administration following cord clamping confers an increased SSI risk to the mother. Methods Study design: Cohort. Setting: 75 participating Swiss hospitals, from 2009 to 2018. Participants: A total of 55,901 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…While the microbiome effects of IAP are difficult to disentangle from the effects of CS, it is likely that neonatal antibiotic exposure in our study could have detrimentally affect the viability of ‘seeded’ microbes, thereby reducing their likelihood of successful colonisation. Delaying IAP administration until after cord clamping may help mitigate these effects and improve gut microbiome development which is particularly pertinent given a recent study of 55,901 women found no differences in surgical site infections depending on whether IAP were administered before or after cord clamping [72] .…”
Section: Discussionmentioning
confidence: 99%
“…While the microbiome effects of IAP are difficult to disentangle from the effects of CS, it is likely that neonatal antibiotic exposure in our study could have detrimentally affect the viability of ‘seeded’ microbes, thereby reducing their likelihood of successful colonisation. Delaying IAP administration until after cord clamping may help mitigate these effects and improve gut microbiome development which is particularly pertinent given a recent study of 55,901 women found no differences in surgical site infections depending on whether IAP were administered before or after cord clamping [72] .…”
Section: Discussionmentioning
confidence: 99%
“…However, current WHO recommendation is to administer prophylactic antibiotic before surgical incision based on meta-analyses concluding that this policy reduces the risk of surgery [ 27 ]. On the contrary, recent large Swiss study did not confirm this finding [ 28 ]. At the time of our study, local hospital guidelines instructed to start prophylactic antibiotics 30–60 min before incision.…”
Section: Discussionmentioning
confidence: 71%
“…It was the largest clinical study on the topic so far. 54 The prevention of maternal infectious complications is highly important. SSIs after birth pose a health risk to mothers, interfere with maternal care for the newborn and often make post-partum antibiotics necessary which can transfer to the infant via breast milk.…”
Section: Discussionmentioning
confidence: 99%